Creative Problem Solving using Algorithmic Methods - Beresnevičius, Gediminas (Acta Paedagogica Vilnensia, 2006)
The article deals with the problem of creative problem solving process. The author makes differences among using already quite popular psychological methods of training of creative thinking such as brain storm, learning by doing mistakes and etc. and algorithmic methods of problem solving. The research confirmed hypothesis that it is possible to develop creative problem solving abilities of the middle aged school teachers using algorithmic methods of problem solving. The research data showed that originality of problem solving among teachers of experimental group was higher (p < 0,05) than the teachers of the same age of control group. The similar results were found comparing effectiveness of problem solving among teachers of experimental group and control groups. Data also revealed that teachers of the control group are not using any method